Pattern of Injuries in Fatal Motorcycle Accidents Seen in Lagos State University Teaching Hospital: An Autopsy-Based Study - Faduyile, Francis; Emiogun, Festus; Soyemi, Sunday; Oyewole, Olugbenga; Okeke, Uche; Williams, Oluseun (Open access Macedonian journal of medical sciences, 2017)
BACKGROUND: Deaths from motorcycle accident injuries have remained a major public health issue in Nigeria over the years.AIM: The study is to determine the age and gender distribution of the victims and to identify the cause of death and the anatomical pattern of injuries seen.METHODOLOGY: This is a 5-year autopsy-based study of all motorcycle accident deaths seen in Lagos State University Teaching Hospital between December 2009 and November 2014. The data were retrieved from autopsy reports, hospital case notes extracts from police diary and were analysed using SPSS version 20.RESULTS: Motorcycle accidents accounted for 156 (2.8%) of all the autopsies done (5,661), and 156 (18.4%) of all Road Traffic Accidents (RTA) autopsies (849) performed over the study period, with a male: female ratio of 6:1. The peak age of victims was 31-40 years (30.9%). Head injuries accounted for most (41.4%) of the injuries seen, and the majority of the victims died of craniocerebral injury 53 (50.7%).CONCLUSION: This study showed that males in the fourth decade of life are the major victims of motorcycle accident death. The majority of the victims were the rider of the motorcycle. Most of them died of the craniocerebral injury.